Index of relative importance of diet components in Mastacembelus armatus (Lacepède, 1800) from Karapuzha Reservoir, Wayanad, Kerala, India - Panikkar, Preetha; Khan, Feroz; Sharma, A. P.; Jha, B. C.; Vijaykumar, M. E. (Indian Journal of Fisheries, 2013)
The dietary analysis of the spiny eel, Mastacembelus armatus showed that the fish subsisted mainly on small forage fishes. The gut contents were analysed using the frequency of occurrence, numerical counts and gravimetric methods. In addition to fishes, the gut content comprised prawns, insects, aquatic plants and digested matter. The index of relative importance (IRI) values indicated that fishes and prawns were the major diet components. Feeding intensity was high in the early maturity stages and was relatively lower in fishes with ripe gonads. The highest feeding intensity was observed during summer months and the lowest coincided with the monsoon months.